Understanding of Plagiarism through Information Literacy: A Study among the Students of Higher Education of Nepal - Adhikari, Prem Raj (Journal of Business and Social Sciences Research, 2018)
The study deals with the issues related to the contribution and the need of information literacy. This study has explored the importance of information literacy in academic work among the Nepali students of higher education. Plagiarism is the technical term for stealing someone else’s intellectual property. The research examined the truth about the understanding about plagiarism and copyright issues in the use of information. This quantitative study is aligned towards positivist paradigm and adopted survey design for data collection. The population of the study was students of higher education of Tribhuvan University, Kathmandu University and Pokhara University. Two hundred and fifty-four (254) sample populations were drawn using sample size formula for data. For this purpose, simple random sampling was used to determine the number of the sample population. The sample population was selected using random sampling procedure. The data were collected using survey method and were analyzed using SPSS descriptive statistics used for the purpose of data analysis. The findings of this study showed that information literacy is important and helpful in academic works in higher education. Students of higher education rely on the internet and library for their academic resources in Nepal. The use of information literacy is expected to be the part of education to make the learning process effective. This study also focused on the use of right information in appropriate ways among the students of higher education of Nepal. Research indicated that there was lack of understanding what students know and use about the supplied information in higher education in Nepal.